Reconstruction of Hypospadias Comparision of Different Techniques (A Study of 45 Cases) - Kumawat, M. L.; Yadav, R. G.; Sadasukhi, T. C.; Chandalea, B. S. (Indian Journal of Plastic Surgery, 1980)
Forty five cases of hypospadias were studied. Of these 80 percent had penile hypospadias, 13 percent penoscrotal and 7 percent perineal hypospadias. Chordae was corrected before 2 years of age in 13.3 percent due to late presentation. The incidence of residual chordae was higher in patients treated by Cecil Culps technique. Plastic repair was completed in preschool age in 31 percent and an cqual number of padents were treated between 5–10 years age. None of the patients reported for second stage reconstruction within 6 months of first operation. Incidence of fistulae formation was 6.6 percent with Byar's Browne and 13.3 percent with Cecil Culp technique.